A Feminist Semiotic Study on the Symbolic Meaning of Femininity in the Book Cover Design: There’s a She-Wolf Inside Every Woman - Ainal Husna; Juwita Wirta Sri Depi; Amelia Isti Fahmi (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
This study explores the symbolic meaning of femininity embedded within the visual elements of the book cover